Accounting for Zakat: Management of Company Zakat in Company Maslahah - Nurhikma Nurhikma; Lince Bulutoding; Puspita H. Anwar (ISAFIR: Islamic Accounting and Finance Review, 2021)
This study aims to determine the understanding of zakat and the urgency of zakat in achieving the benefit of the people (Study at PT Chocolicious Indonesia in Makassar City). This research is a qualitative research that is integrated with a phenomenological approach. Data collection methods using interview and documentation techniques. The data collected is then reduced, analyzed, validated, and a final conclusion is made as a result of the study. The results show that the understanding of zakat in PT Chocolicious Indonesia is very well understood, referring to what has been conveyed in the interviews conducted. Basically, zakat which is the obligation of individuals and groups is a must and this is what PT Chocolicious Indonesia holds firmly as an entity based on sharia principles. Regarding the urgency of zakat, PT Chocolicious Indonesia understands zakat as an obligation that must be distributed and managed properly and on target because it is a form of accountability vertically to Allah Almighty and horizontally to fellow humans